After the crash : assessment and treatment of motor vehicle accident survivors - Blanchard, Edward B. (American Psychological Association, 1997)
Involvement in motor vehicle accidents (MVA) is a widespread experience for Americans. Moreover, a large-scale survey has shown that MVAs are the most frequent trauma for American males and second most frequent trauma for American females. Another large-scale survey found that MVAs were the single leading cause of posttraumatic stress disorder (PTSD) in the general population. Yet very little is known about the assessment and treatment of road crash survivors, and few studies have looked at the psychological and psychosocial effects of surviving an accident. This book describes the details of a 5-yr study of MVA survivors in the Albany, New York area and discusses MVA related PTSD. This volume will appeal to a broad audience of practitioners, researchers, and physicians; attorneys who handle MVA survivor cases; and those interested in public safety issues. (PsycINFO Database Record (c) 2004 APA, all rights reserved).